Simulation of denitrification and ozone loss for the Arctic winter 2002/2003 - Grooss, J.-U.; Günther, G.; Müller, R.; Konopka, P.; Bausch, S.; Schlager, H.; Voigt, C.; Volk, C. M.; Toon, G. C. (HAL CCSD, 2004)
International audience We present simulations with the Chemical Lagrangian Model of the Stratosphere (CLaMS) for the Arctic winter 2002/2003. We integrated a Lagrangian denitrification scheme into the three-dimensional version of CLaMS that calculates the growth and sedimentation of nitric acid trihydrate (NAT) particles along individual particle trajectories. From those, we derive the HNO 3 downward flux resulting from different particle nucleation assumptions. The simulation results show a clear vertical redistribution of total inorganic nitrogen (NO y ), with a maximum vortex average permanent NO y removal of over 5 ppb in late December between 500 and 550 K and a corresponding increase of NO y of over 2 ppb below about 450 K. The simulated vertical redistribution of NO y is compared with balloon observations by MkIV and in-situ observations from the high altitude aircraft Geophysica. Assuming a globally uniform NAT particle nucleation rate of 3.4·10 ?6 cm ?3 h ?1 in the model, the observed denitrification is well reproduced. In the investigated winter 2002/2003, the denitrification has only moderate impact (?10%) on the simulated vortex average ozone loss of about 1.1 ppm near the 460 K level. At higher altitudes, above 600 K potential temperature, the simulations show significant ozone depletion through NO x -catalytic cycles due to the unusual early exposure of vortex air to sunlight.